Superconductivity below 20 K in heavily electron-doped surface layer of FeSe bulk crystal - J. J. Seo (Nature Portfolio, 2016)
Thin FeSe film on SrTiO3 substrate becomes a superconductor with a transition temperature over 100 K, yet the origin remains controversial. Here, Seo et al. show superconductivity below 20 K on the electron-doped surface of an FeSe crystal, suggesting a decisive role of interfacial effects in the enhancement of superconductivity.